Possible factors which produce fruit drop of Myrciaria dubia (HBK) Mc Vaugh, "camu camu" during the reproductive phenology in the collection “cinco cuencas” from the San Miguel experimental center- IIAP, Loreto, Peru (Scientia Agropecuaria, 2010)
"Camu camu" plants were evaluated in five basins in Loreto (Peru), according to the percentage of fruits with symptoms of pest infestation, retention of flowers and fruits in each basin, diameters of branches, and the influence of precipitation and temperature in the process of falling fruit as the phenological stage. In the genetic factor, the Putumayo river basin highlighted by a longer retention of fruit, higher yield and average fruit weight and less attack by pests. During the phenological process that lasted 12 weeks, the critical stage of flower and fruit drop occurred during the first seven, with the retention of flowers of 5.12%. The pests are causing the observed fall 9.27%, 9.15% being caused by Edessa sp., And 0.12% for Conotrachellus dubiae. The other 90.73% was caused by other undetermined factors such as physiological, nutritional, competition, wind, rain. Environmental factors of temperature and precipitation have a direct influence and inversely proportional to the fall of fruits, respectively.
Keywords: Fruit growing; camu camu; Myrciaria dubia; genetic improvement; fruit drop; physiology